In vivo axial humero-ulnar rotation in normal and dysplastic canine elbow joints - Rohwedder, Thomas; Fischer, Martin; Böttcher, Peter (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2018)
Objective: To prospectively compare relative axial (internal-external) humero-ulnar rotation in normal and dysplastic canine elbow joints.Material and methods: Six normal elbows (five dogs) and seven joints (six dogs) with coronoid disease were examined. After implantation of 0.8 mm tantalum beads into humerus and ulna, biplanar x-ray movies of the implanted elbows were taken while dogs were walking on a treadmill. Based on the 2D bead coordinates of the synchronized x-ray movies virtual 3D humero-ulnar animations were calculated. Based on these, relative internal-external humero-ulnar rotation was measured over the first third of stance phase and expressed as maximal rotational amplitude. Amplitudes from three consecutive steps were averaged and groupwise compared using an unpaired t-test.Results: In normal elbow joints mean axial relative humero-ulnar rotation was 2.9° (SD 1.1). Dysplastic joints showed a significantly greater rotational amplitude (5.3°, SD 2.0; p = 0.0229, 95% confidence interval 0.4–4.4).Conclusion: Dysplastic elbow joints show greater relative internal-external humero-ulnar rotation compared to normal elbows, which might reflect rotational joint instability.Clinical relevance: Increased relative internal-external humero-ulnar rotation might alter physiological joint contact and pressure patterns. Future studies are needed to verify if this plays a role in the pathogenesis of medial coronoid disease.
Keywords: Fluoroscopy; kinematics; kinematography; elbow dysplasia; medial coronoid disease